Contemporary Spanish politics of memory (1999-2014) = Współczesna hiszpańska polityka pamięci (1999-2014) - Opioła, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, the analysis and an attempt to systematize the contemporary Spanish politics of me-mory. The axis of the current debates about the past are in Spain two events: the Spanish Civil War (1936-1939) and Franco?s dictatorship (1936-1975). The starting point for discussion is the thesis of the distributed nature of initiatives seeking to dominate the politics of memory.
Keywords: historical memory; Spanish Civil War; politics of memory of Spain; civil society; pamięć historyczna; hiszpańska wojna domowa; polityka pamięci Hiszpanii; społeczeństwo obywatelskie